KEEFEKTIFAN MEDIA GAMBAR DIAM TERHADAP MENULIS HANZI 汉字 SISWA KELAS VI SD FRATER MAKASSAR - Dian Fitriani; Nurming Saleh; Misnawaty Usman (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2021)
This research is quasi-experimental research, the research is to find out the effectiveness of picture media on writing hanzi of six grades’ students at Frater Elementary School Makassar. Sample of the research were 14 students in experimental group and 14 students in control group, which was the total sampling. This data research obtained by writing hanzi test and was analyzed using t-test. The result of this research shows that tcount is higher than ttable (4.374 > 2.056) significant level of 0.05. The use of picture media is effective on writing hanzi of six grades’ students at Frater Elementary School Makassar.Keywords: Effectiveness, Picture Media, Writing, Chinese.